2014
DOI: 10.1155/2014/718946
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL-17, IL-23, and TGF-βLevels in Type 1 and Type 2 Diabetic Patients and Age-Matched Healthy Controls

Abstract: Type 1 diabetes is recognized as an autoimmune inflammatory disease and low grade inflammation is also observed in type 2 diabetic patients. Interleukin 17 (IL-17) is a new player in inflammation. Th17 cells, as the main source of IL-17, require transforming growth factor β (TGF-β) and interleukin 23 (IL-23). The aim of this study was to investigate serum IL-17, IL-23 and TGF-β levels in diabetic patients and controls. In this case-control study, serum levels of IL-17, IL-23, and TGF-β were measured in 24 type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 45 publications
5
40
0
1
Order By: Relevance
“…IL-4, IL-6 and IL-13 appeared higher in diabetic groups, but no difference between EV 1 and EVwas observed. Human serum TGF-b levels were also decreased in diabetic children with either types 1 or 2 [14]. Increased levels of IL-4 and IL-6 in hyperglycaemic T1D children were found sustained even after 2 h of euglycaemia/correction [39].…”
Section: Discussionmentioning
confidence: 88%
“…IL-4, IL-6 and IL-13 appeared higher in diabetic groups, but no difference between EV 1 and EVwas observed. Human serum TGF-b levels were also decreased in diabetic children with either types 1 or 2 [14]. Increased levels of IL-4 and IL-6 in hyperglycaemic T1D children were found sustained even after 2 h of euglycaemia/correction [39].…”
Section: Discussionmentioning
confidence: 88%
“…The role of IL17 on the risk for type 2 DM remains unclear. Roohi A et al [41] reported no association between serum IL17 levels and type 1 and 2 diabetes. Another study found that therapeutic improvement of glucoregulation in newly diagnosed type 2 DM patients is associated with a reduction of IL-17 levels [42].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Th17 cells were higher in patients that presented more T2D complications[57]. Conversely, no differences were found in IL-17 plasma of T2D compared to age-matched healthy controls[61]. …”
Section: Role Of Th17 Cells In the Progression From Nafld To Nashmentioning
confidence: 99%
“…They showed higher percentages of Th17 cells in the peripheral blood in comparison with healthy lean children[61]. In other pediatric diseases these T cells were involved, principally in inflammation, such as autoimmune thyroid disease or Mycoplasma pneumoniae infection[65,66] (Table 3).…”
Section: Role Of Th17 Cells In the Progression From Nafld To Nashmentioning
confidence: 99%